2015
DOI: 10.3390/ijms160613356
|View full text |Cite
|
Sign up to set email alerts
|

Targeted siRNA Screens Identify ER-to-Mitochondrial Calcium Exchange in Autophagy and Mitophagy Responses in RPE1 Cells

Abstract: Autophagy is an important stress response pathway responsible for the removal and recycling of damaged or redundant cytosolic constituents. Mitochondrial damage triggers selective mitochondrial autophagy (mitophagy), mediated by a variety of response factors including the Pink1/Parkin system. Using human retinal pigment epithelial cells stably expressing autophagy and mitophagy reporters, we have conducted parallel screens of regulators of endoplasmic reticulum (ER) and mitochondrial morphology and function co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 60 publications
1
33
0
Order By: Relevance
“…It has been suggested that cytosolic Ca 2+ levels are one of the factors contributing to mitophagy (East & Campanella, ; Rimessi et al , ). For example, MacVicar et al () demonstrated that treatment with the Ca 2+ chelator BAPTA‐AM blocked CCCP‐induced mitophagy and suggested that transient and local Ca 2+ spikes might be needed for mitophagy. Cherra et al () demonstrated that excess cytosolic Ca 2+ is associated with profound mitophagy and that restoring Ca 2+ homeostasis through Ca 2+ chelation or inhibition of voltage‐gated Ca 2+ channels was sufficient to prevent the mutant LRRK2 phenotype related to Parkinson disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that cytosolic Ca 2+ levels are one of the factors contributing to mitophagy (East & Campanella, ; Rimessi et al , ). For example, MacVicar et al () demonstrated that treatment with the Ca 2+ chelator BAPTA‐AM blocked CCCP‐induced mitophagy and suggested that transient and local Ca 2+ spikes might be needed for mitophagy. Cherra et al () demonstrated that excess cytosolic Ca 2+ is associated with profound mitophagy and that restoring Ca 2+ homeostasis through Ca 2+ chelation or inhibition of voltage‐gated Ca 2+ channels was sufficient to prevent the mutant LRRK2 phenotype related to Parkinson disease.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that the downregulation of the PINK1 gene did not significantly change the cell growth rate, which is consistent with the results of previous research. 36 Different responses between wild-type cells and PINK1 gene knockdown cells to ZnO NP exposure were observed, and the results suggested that the downregulation of PINK1 caused a significant reduction in the survival rate after ZnO NP exposure compared with that of control cells. These results indicated that the PINK1 gene may not be an essential factor in the survival of BV-2 cells but that it possibly exerts a function in the defense of ZnO NP stimulation.…”
mentioning
confidence: 98%
“…S1R was also reported to interact with G-protein coupled receptors (see review) [12]. Recently, evidence showed that S1R is involved in autophagy [31, 32]. In accordance, S1R also participates in ER stress responses; e.g., S1R interacts with and stabilizes ER stress sensor IRE1 [29, 33, 34].…”
Section: General Molecular Functions Of S1rmentioning
confidence: 99%
“…Nevertheless, in an earlier study using a human RPE cell line (ARPE-19) and adult human primary RPE cells, Bucolo et al were able to reduce H 2 O 2 -induced DNA damage and cell loss by pre-treatment with PRE084, an effect abolished by S1R antagonists [71]. Most recently, using targeted siRNA screening in a human RPE1 cell line, MacVicar et al identified S1R as a potential regulator of autophagosome homeostasis involving mitochondrial dynamics [31]. Autophagy is an important stress response pathway responsible for the removal and recycling of damaged or redundant cytosolic constituents.…”
Section: Functions Of S1r In the Retinamentioning
confidence: 99%
See 1 more Smart Citation